Equality and Diversity Policy in the British Public Sector: Narrowing the Gender Pay Gap? - Gupta, Nidhi (2008)
This study aims to analyze the effect of equality and diversity policies on the gender pay gap in UK public sector. The study is evaluated using secondary data from Labour Force Surveys (LFS), Annual Survey of Hours and Earnings (ASHE) and Workplace Employees Relations Survey (WERS) which compares the presence of equality and diversity policies with the simultaneous gender pay gap in UK public sector in order to determine the extent to which these policies have affected the gender pay gap in UK public sector.